1991
DOI: 10.3109/00207459108999775
|View full text |Cite
|
Sign up to set email alerts
|

The Pineal Gland and Spontaneous Abortions: Implications for Therapy with Melatonin and Magnetic Field

Abstract: Spontaneous abortion, the termination of pregnancy prior to 20 weeks of gestation, is estimated to occur in 40%-50% of all pregnancies and in 12%-15% of identified pregnancies. The causes of spontaneous abortion can be divided into two main categories: those arising from chromosomal anomalies and those arising from abnormalities in the intrauterine environment. In the following communication, we propose that deficient pineal melatonin functions in early pregnancy may be causally related to the development of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
0
12
0
3
Order By: Relevance
“…In addition, endogenous melatonin can influence the secretion of other hormones with neuroprotectiveactivity. One such hormone is progesterone;ithas been shown to be neuroprotective (37),and itssecretionmight be stimulatedby melatonin (38).Others may include the adrenal hormones (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, endogenous melatonin can influence the secretion of other hormones with neuroprotectiveactivity. One such hormone is progesterone;ithas been shown to be neuroprotective (37),and itssecretionmight be stimulatedby melatonin (38).Others may include the adrenal hormones (18).…”
Section: Discussionmentioning
confidence: 99%
“…During normal pregnancy, melatonin acts as an antioxidant and appears to be essential for a successful pregnancy. Sandyk et al had found the association of melatonin and spontaneous abortion which was presumed to be due to melatonin’s role in diminishing uterine contractions by decreasing the production of prostaglandins and in prevention of the immunologic rejection of trophoblast by stimulating the progesterone production [31]. Further, Matsuzuka et al showed that alleviation of the embryo death might be achieved by administration of melatonin in mice [32].…”
Section: Physiological Functions Of Melatonin During Pregnancymentioning
confidence: 99%
“…For instance, maternal plasma melatonin levels are elevated during pregnancy, reaching a maximum at term and then returning to basal levels soon after delivery. Concentrations of melatonin in maternal plasma are also higher in twin than in single pregnancies [12–15]. The expression of melatonin receptors in the human and rat placenta further suggests that melatonin plays a functional role in feto‐placental development [16–18].…”
Section: Introductionmentioning
confidence: 99%